2010
DOI: 10.1128/aac.00177-10
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Linezolid: a Retrospective Monocentric Analysis

Abstract: The objective of the present retrospective observational study carried out in patients receiving a standard dosage of linezolid and undergoing routine therapeutic drug monitoring (TDM) was to assess the interindividual variability in plasma exposure, to identify the prevalence of attainment of optimal pharmacodynamics, and to define if an intensive program of TDM may be warranted in some categories of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
130
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(146 citation statements)
references
References 36 publications
9
130
3
1
Order By: Relevance
“…Therefore, treatment with a fixed dose may be questionable (6,11,22,26). The application of TDM for linezolid can help avoid under-or overexposure, which may occur in 30 to 40% of the cases (20). In this study, all patients had Mycobacterium tuberculosis isolates with a linezolid MIC of Յ0.5 mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treatment with a fixed dose may be questionable (6,11,22,26). The application of TDM for linezolid can help avoid under-or overexposure, which may occur in 30 to 40% of the cases (20). In this study, all patients had Mycobacterium tuberculosis isolates with a linezolid MIC of Յ0.5 mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with two recent studies about linezolid pharmacokinetics (PK). The first one analyzed the C min of linezolid in 92 patients, and 29% had a C min below the MIC 90 of linezolid (6). The second experiment was performed in 8 critically ill patients who received linezolid at 600 mg/12 h, and 50% of them had a linezolid C min Ͻ 1 mg/liter (8).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of linezolid in a compassionate use program, a higher success rate was observed when concentrations remained above the MIC for the entire dosing interval and when AUC 24 /MIC values were 80 to 120 (5). Some recent data suggest that the linezolid trough plasma concentration (C min ), in some patients, is below the MIC 90 of linezolid for staphylococci (6).…”
mentioning
confidence: 99%
“…Some data suggest that linezolid inhibits its own metabolism [80], therefore prolonged treatment is associated with a progressive increase in serum concentrations that are associated with haematological toxicity [81,82]. The linezolid toxic trough is not well defined but supposedly should not be >8 mg/L (ideally 2-7 mg/L), and therapeutic drug monitoring (TDM) should probably be performed in certain circumstances [79,81]. A recent study analysed the trough concentrations in consecutive patients and found a mean trough of 9 mg/L in patients who developed haematological toxicity compared with 4 mg/L in those without toxicity [82].…”
Section: Prolonged Use Of Linezolidmentioning
confidence: 99%